Artificial intelligence and the constitutional duty to protect the environment: the responsibility for the Brazilian State's technological inertia (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
This study analyzes the constitutional duty of environmental protection through artificial intelligence, proposing that the State be held accountable for technological inaction in the face of international climate commitments.(Received: October 2025 | Accepted: November 2025)
Keywords: Constitutional Duty; Artificial Intelligence; Socio-environmental State; Civil Liability; Environmental Protection